Interfaces amigáveis para consultores comerciais realizarem negócios digitais: estudo de caso com corretores de seguros - Costa, Albert Florencio da (2017)
This study presents an analysis of friendly interfaces for Internet systems, which facilitates the use of commercial consultants (non-technical) in creating digital business. The objective of this study is to verify the importance of friendly digital platforms so that lay commercial consultants are not eliminated from the market, in the current environment where digital businesses are growing every day. Through a bibliographic review, presenting the current scenario in which the commercial consultants beds are inserted, as well as the technical requirements necessary to build a good interface, we analyze the use of the Interface (OnCorretor) offered by the company Porto Seguro to its Insurance Brokers Who are the commercial consultants of this market. We conclude that the OnCorretor is a platform that meets the brokers business expectations, accessible including being by lay users, allowing them to build their own websites with your domain, manage email accounts, manage online proposals, interact with their customers. The OnCorretor platform has a user-friendly interface that makes it easy to use, but some users still have questions about how to get the best results in their business. In this way, we suggest that an online training, as well as a greater use of interaction with social networks, be made available to the user whenever he needs it. We also suggest periodic surveys for the maintenance and optimization of your business, with presence on the Internet and on social networks. The most important finding is that the user-friendly interface is simple to use for 75.6% of respondent brokers and 63.2% of them understand that it has helped to optimize their business. We suggest that other companies in the insurance industry or other using consultants commercial to develop similar platforms based on this model